Estudio de tres fuentes de proteína vegetal, Lens culinaris (Lenteja), Cicer arietinum (Garbanzo) y Glycine max (Soja) en sustitución parcial de la proteína animal para la elaboración de embutidos de pasta fina (salchicha tipo vienesa) - Solórzano Castro, Bryan Miguel (2019)
ABSTRACT The present research work was based on the partial substitution of animal protein using Lens culinaris (lentil), Cicer arietinum (chickpea) and Glycine max (soybean) for the preparation of fine pasta sausages (Viennese type sausage), for which Three sources of vegetable protein were used using two percentages (50 and 60%). In addition, the nutritional characteristics of the sausage were evaluated by means of physicochemical and microbiological analyzes such as: protein, ash, fat, pH, titrable acidity, Escherichia Coli and total Coliforms. The organoleptic characteristics of the product prepared by sensorial evaluation were also analyzed, which was determined by students of the eighth semester of Agroindustrial Engineering with their respective tasting sheets to establish which of the treatments applied gives the best results. The analyzes were carried out in the bromatology laboratory of the La María Experimental Farm and in the tasting room located in the UTEQ basic laboratory. In the statistical analysis of this research, an experimental design of completely random blocks with factorial arrangement A * B was used. The factors of study were: Factor A protein sources, Lens culinaris (lentil), Cicer arietinum (chickpea) and Glycine max (soybean) and Factor B percentages of vegetable protein (50 and 60%) that responds to a total of 6 treatments with 3 replicas that gives a total of 18 experimental units. The analysis of the data was carried out in the STATGRAPHICS statistical package program, in addition to the separation of means from the levels of the treatments, the significance test of TUKEY was used. Key words: Vegetable protein, percentages, tasting, organoleptic, total coliforms.